REPRESENTATION OF FEMALE SUBJECTIVITY IN THE SHORT STORY THE PEACE OF UTRECHT, BY ALICE MUNRO - Bazzoli, Oise de Oliveira Mattos [UNESP] (Univ Estado Mato Grosso, 2024)
The aim of this paper is to analyze the short story The Peace of Utrecht from the book Dance of the Happy Shades (1968), to show how the construction of subjectivity in the fiction of the Canadian writer Alice Munro taking into consideration the question of patriarchalism and the relation between the Canadian wilderness and the perspective of women. The analysis will have as theoretical foundation, the considerations of Kehl (1998) regarding femininity, Howells (1998) and the unquestionable character of the sociocultural element represented in literature, among other theorists.
Keywords: Alice Munro; female subjectivity; Canadian literature